Application of boundary element method for the analysis of potential flow field and wave resistance in finite depth of water - Md. Shahjada, Tarafder; Gazi, Md. Khalil (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/